2019
DOI: 10.3390/molecules24030556
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Mitogen-Activated Protein Kinase SlMAPK3 Positively Regulates Tomato Tolerance to Cadmium and Drought Stress

Abstract: Mitogen-activated protein kinases (MAPKs) activation is a common defense response of plants to a range of abiotic stressors. SlMPK3, a serine-threonine protein kinase, has been reported as an important member of protein kinase cascade that also functions on plant stress tolerance. In this study, we cloned SlMPK3 from tomato and studied its role in cadmium (Cd2+) and drought tolerance. The results showed that transcripts of SlMAPK3 differentially accumulated in various plant tissues and were remarkably induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 93 publications
3
37
0
Order By: Relevance
“…Many researchers have previously demonstrated the multifaceted importance of metallic TEs in higher plants. Examples include the gene regulation [17], cell signaling [18], secondary metabolites formation [19], CO 2 assimilation and stomatal conductance [20], and transport across vascular bundles [21]. Therefore, the biological role of each TE is out of discussion in the present review that concerns the recent findings only on elements that are considered as heavy metals or metalloids.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have previously demonstrated the multifaceted importance of metallic TEs in higher plants. Examples include the gene regulation [17], cell signaling [18], secondary metabolites formation [19], CO 2 assimilation and stomatal conductance [20], and transport across vascular bundles [21]. Therefore, the biological role of each TE is out of discussion in the present review that concerns the recent findings only on elements that are considered as heavy metals or metalloids.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the accumulation of ROS in detached leaves increased. A large amount of ROS can cause toxicity to plant cells, which can destroy biological macromolecules, attack cell membranes, and accelerate leaf damage [ 33 ]. In this experiment, the accumulation of ROS in the leaves of W. chinensis was the highest, and that in the leaves of W. trilobata was the lowest, indicating that the leaves of W. chinensis were under the most serious oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…ClO2 treatment has been demonstrated to delay pericarp browning in longan fruit by upregulating gene expression of the antioxidant defense-related enzymes such as superoxide dismutase, catalase and ascorbate peroxidase in harvested longan during storage at room temperature (Chomkitichai, 2014). This upregulation may be a result of activation through MPK3 and MPK6 by H2O2 signaling (Muhammad et al, 2019). In addition, the H2O2 signaling also affects Prx-Trx system causing an increase in the NADPH/NADP ratio.…”
Section: Discussionmentioning
confidence: 99%